Modifications of ZnO Interlayer to Improve the Power Conversion Efficiency of Organic Photovoltaic Cells: A Review - Jayaram, Divya; Goyal, Aditi; Naik, Durva; Goswami, Prerna; Kerawalla, M.A.K. (Asian Journal of Chemistry, 2017)
Power conversion efficiency (PCE) is an important parameter in determining the performance of organic photovoltaics (OPVs). Various factors lead to enhancement of power conversion efficiency. One such factor is doping of electron transport layer. A substantial increase in the power conversion efficiency of inverted organic solar cells is realized by a ZnO doped buffer layer acting as an electron-transport layer. Different works on Li, Cd, Ga, Al doping, introduction of C60 interface layer in ZnO buffer layer and dual doped system of InZnO-BisC60 have been reviewed here. The Al-doped buffer layer device showed the highest increase in power conversion efficiency.